Diacylglycerol Kinase ε in Adipose Tissues: A Crosstalk Between Signal Transduction and Energy Metabolism - Nakano, Tomoyuki; Goto, Kaoru (Frontiers in Physiology, 2022)
Diacylglycerol (DG) is unique in lipid metabolism because it serves not only as an intermediate product for triglyceride synthesis, but also as a signaling molecule that activates proteins containing DG-responsive elements, such as protein kinase C. Consequently, DG acts as a hub between energy metabolism and intracellular signaling. Of DG metabolizing pathways, DG kinase (DGK) phosphorylates DG to produce phosphatidic acid, which also serves as a second messenger. Several lines of evidence suggest that DGK is deeply involved in metabolic diseases such as obesity and insulin resistance. Of DGK isozymes, DGKε is simplest in terms of structure, but it is characterized by substrate specificity toward arachidonoyl-DG. Recently, we have reported that DGKε deficiency promotes adipose tissue remodeling in mice during the course of high fat diet (HFD) feeding regimen including obesity, insulin resistance, and beige adipogenesis. DGKε ablation engenders altered expression of other lipid metabolizing enzymes, including adipose triglyceride lipase (ATGL), hormone-sensitive lipase (HSL), and diacylglycerol acyltransferase (DGAT). Subcellular localization of DGKε in the endoplasmic reticulum suggests involvement of this isozyme in lipid energy homeostasis. This review presents current findings of DGKε in lipid-orchestrated pathophysiology, especially unique phenotypes of DGKε-knockout mice in the early and late stages of obesogenic conditions.